Prediction Analysis of Buled Bread Production Using Holt's Exponential Smoothing - Budianto, Heru; Darmawan, Erlan; Krisdiawan, Rio Andriyat; Maulana, Yasir (International Journal Administration, Business & Organization, 2024)
This research aim to Analysis of Buled Bread Production Using Holt's Exponential Smoothing. The number of loaves produced by Buled bread still uses estimates, causing the number of loaves produced to be excessive. The excess number of loaves produced increases production costs, which can cause losses. The method broadcast in forecasting is Holt's exponential smoothing because the data displayed shows an increasing trend that is not affected by the season. The calculation process uses Microsoft Excel and add-ins. The results of the calculation produce a Mean Absolute Percentage Error (MAPE) value of 3.58% so that it can be used to forecast production data in the following month. The value of α = 0.8808 and the value of β = 0.042 are the best values ​​based on calculations using the Solver Add-in. Based on these parameter values, predictive data is produced for each week in the following month.